The mechanism of miR-525-5p derived from hypoxia and reoxygenation in H9c2 Cardiomyocytes - Wang, Shanshan; Xin, Mei; Song, Ronggang; Meng, Hongyan; Wei, Xinfeng (Cellular and Molecular Biology, 2022)
Ischemia-reperfusion injury (IRI) is associated with ischemic heart disease (IHD) which leads to patients a poor progression. According to Pubmed Datasets, we analyzed different gene and mRNA expressions in IHD patients with IRI. The relevant mRNA expression detected in H9C2 cells undergo hypoxia and reoxygenation, we selected and structured miR-525-5p gene mutation H9C2 cells, the results performed miR-525-5p mutated restored H9C2 metabolism of mitochondria which detected by relevant genes and proteins. At the same time, miR-525-5p silence resisted hypoxia and reoxygenation induced H9C2 cells apoptosis. All the results indicated miR-525-5p maybe protect H9C2 cells without hypoxia and reoxygenation induced injury through regulating the mitochondria metabolism.